Effect of DNA damage and oxidative stress on peripheral blood cells induced by marathon running - Liu, X.; Su, M.; Shen, F. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper investigates the DNA damage and the anti-oxidative status of human peripheral blood cells at different times following marathon running. The effects and mechanism of DNA damage induced by extensive endurance exercise are also discussed. It is anticipated the present findings will provide a scientific basis for evaluating training status and fatigue levels in athletes.